Gas chromatographic separation of fatty acid esters of cholesterol and phytosterols on an ionic liquid capillary column - Hammann, Simon; Vetter, Walter (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2015)
Steryl esters are high molecular weight compounds (600–700 g/mol) regularly present as a minor lipid class in animal and plant lipids. Different sterol backbones (e.g., cholesterol, β-sitosterol and brassicasterol) which can be esterified with various fatty acids can result in highly complex steryl ester patterns in food samples. The gas chromatographic (GC) analysis of intact steryl esters is challenging, since high elution temperatures are required for their elution. On nonpolar GC phases, steryl esters with fatty acids with differing degree of unsaturation (e.g., oleate and linoleate) cannot be separated and there are only few polar columns available with sufficient temperature stability. In this study, we used gas chromatography with mass spectrometry (GC/MS) and analyzed intact steryl esters on a commercial room temperature ionic liquid (RTIL) column which was shortened to a length of 12 m. The column separated the steryl esters both by total carbon number and by degree of unsaturation of the fatty acid. For instance, cholesteryl esters with stearic acid (18:0), oleic acid (18:1n-9), linoleic acid (18:2n-6) and α-linolenic acid (18:3n-3) could be resolved (R ≥ 1.3) from each other. By analysis of synthesized standard substances, the elution orders for different steryl backbones and different fatty acids on a given sterol backbone could be determined. Analysis of spreads and plant oils allowed to determine retention times for 37 steryl esters, although a few co-elutions were observed. The ionic liquid column proved to be well-suited for the analysis of intact steryl ester
Keywords: Gas chromatography; Ionic liquid; Mass spectrometry; Steryl ester